Exploring Community Resilience, Emotional Solidarity and Place Attachment for Disaster Preparedness (Case Study: Rural Destination in West Sumatera) - Mustafa, Nadya; Sari Lenggogeni; Yulia Hendri Yeni (Dinasti Review, 2025)
This research explores community resilience, emotional solidarity, and place attachment in disaster preparedness at rural tourist destinations in West Sumatra. Using a qualitative approach, data were collected through in-depth interviews with stakeholders, including village tourism managers, disaster activists, and community representatives. The research results show that place attachment and emotional solidarity play an important role in building community resilience to disasters. Factors such as disaster mitigation, social support, and the readiness of infrastructure and regulations are key in strengthening community preparedness. This study provides in-depth insights for tourism destination managers and policymakers in designing more effective strategies for community-based disaster preparedness.